Access to Dental Services among Hypertensive Elderly in Peru: Exploring Patterns and Implications - Ramirez-Ortega, Andrea P.; Vera-Ponce, Víctor Juan; Iturregui Paucar, Cori Raquel (International Journal of Statistics in Medical Research, 2023)
Background: This study was conducted to determine access to dental services in the elderly with hypertension in Peru. Methods: Observational, analytical, and cross-sectional design. Data used for analysis in this research was collected from the Demographic and Family Health Survey of Peru (ENDES) from 2019 to 2021. Results: A Poisson regression analysis was performed a weighted sample for calculating prevalence ratio (PR) with their 95% confidence intervals (95%CI). The multiple regression analysis did not find among the factors associated with the probability of using the dental health service, since neither the time less than two years of hypertension (PR=0.74, 95%CI 0.53 – 1.02); nor from 2 to 4 years (PR = 0.97, CI 95% 0.86 – 1.09); neither a time of hypertension from 5 years or more (PR = 0.94, CI 95% 0.85 – 1.03) were associated. Conclusion: The study concluded that hypertensive patient over 60 years of age, despite a previous diagnosis of hypertension or not, does not attend dental service, reflecting a lack of interest and a greater risk exposure to cardiovascular complications associated with oral health.